2020
DOI: 10.3389/fpsyt.2020.565520
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Burnout, and Coping Strategies of Frontline Nurses During the COVID-19 Epidemic in Wuhan and Shanghai, China

Abstract: Background: Nurses at the frontline of caring for COVID-19 patients might experience mental health challenges and supportive coping strategies are needed to reduce their stress and burnout. The aim of this study was to identify stressors and burnout among frontline nurses caring for COVID-19 patients in Wuhan and Shanghai and to explore perceived effective morale support strategies. Method: A cross-sectional survey was conducted in March 2020 among 110 nurses from Zhongshan Hospital, Shanghai, who were deploye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
257
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(351 citation statements)
references
References 41 publications
25
257
0
12
Order By: Relevance
“…After the screening of the titles and abstracts, we removed 191 records and we added 4 more records found by the reference lists scanning. Finally, we included 14 studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40] in this systematic review that met our inclusion criteria and among them six studies in the meta-analysis that included the appropriate data.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…After the screening of the titles and abstracts, we removed 191 records and we added 4 more records found by the reference lists scanning. Finally, we included 14 studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40] in this systematic review that met our inclusion criteria and among them six studies in the meta-analysis that included the appropriate data.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…Main characteristics of the 14 studies included in our systematic review are shown in Table 1. Study population included only nurses in five studies, 27,28,33,36,40 while nine studies [29][30][31][32]34,35,[37][38][39] included HCWs in general. A total of 17,390 nurses were included in this systematic review, while two studies 37,38 did not report the number of nurses.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations